2011
DOI: 10.1007/s00330-011-2238-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the preoperative assessment of patients with primary breast cancer: systematic review of diagnostic accuracy and meta-analysis

Abstract: MRI shows high diagnostic accuracy, but MRI findings should be pathologically verified because of the high FP rate. Future research on this emerging technology should focus on patient outcome as the primary end-point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(139 citation statements)
references
References 70 publications
11
120
2
6
Order By: Relevance
“…COMICE trial detected 16% of multifocal tumors 13 . The contralateral tumor rates found in our series were similar to other series 23,[27][28][29] . From the additional lesions suspect of malignancy detected through MRI, 68% were positive on the anatomopathological exam.…”
Section: Discussionsupporting
confidence: 92%
“…COMICE trial detected 16% of multifocal tumors 13 . The contralateral tumor rates found in our series were similar to other series 23,[27][28][29] . From the additional lesions suspect of malignancy detected through MRI, 68% were positive on the anatomopathological exam.…”
Section: Discussionsupporting
confidence: 92%
“…[16][17][18] We found that the ICDRs using BWBUS and DCE MRI significantly increased for ER-positive and triple-negative index cancers, but not for HER2-positive index cancers, compared with the ICDRs using mammography. This finding contrasts with a recent study reporting that pre-operative MRI may benefit patients with HER2-positive tumours most, as there is an increased likelihood of the presence of additional disease.…”
Section: Discussionmentioning
confidence: 70%
“…[4][5][6][7][8][9][10][11][12][13][14][15] Systematic reviews of the literature found that pre-operative MRI detected additional ipsilateral disease in 16-20% of patients and occult synchronous contralateral cancer in 4-5% of patients. [16][17][18] Despite the widespread use of breast MRI for pre-operative staging in recent years, this use remains controversial. There is a lack of evidence of long-term benefits from routine breast MRI for pre-operative staging.…”
Section: Introductionmentioning
confidence: 99%
“…12 A recently published meta-analysis confirmed these data, showing similar percentages (12% and 3%, respectively) based on a larger number of studies. 18 Asian breast density is known to be greater than in Caucasians, which is evident on both physical examination and imaging. 15,16 Moreover, MRI further enhances the distinction between normal and diseased breast tissue.…”
Section: Discussionmentioning
confidence: 99%